2007
DOI: 10.1074/jbc.m609711200
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin-3A and Semaphorin-3F Work Together to Repel Endothelial Cells and to Inhibit Their Survival by Induction of Apoptosis

Abstract: Semaphorin-3A (sema3A) is a neuropilin-1 (np1) agonist. It inhibits the binding of the 165-amino acid form of VEGF (VEGF 165 ) to np1 and was reported to inhibit angiogenesis as a result. However, we find that sema3A concentrations that inhibit the mitogenic effects of VEGF 165 do not inhibit VEGF 165 -induced phosphorylation of VEGF receptor-2 (VEGFR-2). Furthermore, sema3A inhibits the biological effects of VEGF 121 , a VEGF form that does not bind to neuropilins and basic fibroblast growth factor, a growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
233
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(248 citation statements)
references
References 39 publications
12
233
3
Order By: Relevance
“…However, recent reports have shown that Sema3s and VEGF use different domains on Nrp1 for binding [40]. Consistent with a separate function of Sema3A on Nrp1, Sema3A increases vascular permeability, inhibits endothelial cell proliferation, and induces apoptosis even in the absence of VEGF [34,41], suggesting Sema3A activates its own signaling routes. Interestingly, Sema3A impairs endothelial cell adhesion and migration by inhibiting integrin function [32].…”
Section: Sema3amentioning
confidence: 73%
See 1 more Smart Citation
“…However, recent reports have shown that Sema3s and VEGF use different domains on Nrp1 for binding [40]. Consistent with a separate function of Sema3A on Nrp1, Sema3A increases vascular permeability, inhibits endothelial cell proliferation, and induces apoptosis even in the absence of VEGF [34,41], suggesting Sema3A activates its own signaling routes. Interestingly, Sema3A impairs endothelial cell adhesion and migration by inhibiting integrin function [32].…”
Section: Sema3amentioning
confidence: 73%
“…Sema3A regulates endothelial cell migration and survival in vitro [33,34], and tumor-induced angiogenesis in vivo [35]. The information emerging from the analysis of Sema3A null mice and mutant mice lacking Sema3A-Nrp1 signaling suggests that Sema3A may not be required for the early stages of developmental angiogenesis, but rather that Sema3A contributes to the reshaping of the vasculature to form a mature vascular network, such as that in the heart and brain [32,36,37].…”
Section: Sema3amentioning
confidence: 99%
“…Because epithelial cells are the primary source of VEGF in lung lavage, an alternative explanation linking conditional epithelial Nrp1 deletion and decreased lavage VEGF concentrations in CS-exposed CCSPrtTA/tetO-Cre/Nrp1 flox/flox mice could be that enhanced epithelial cell death decreases VEGF production. Furthermore, although several investigators have demonstrated that the effects of Nrp1 on cell proliferation and death may depend on how this receptor modulates the balance between VEGF and Sema3 signaling (17,26), other studies also demonstrate that Nrp1 may alter cell survival independent of its effects on VEGFR activation (22,(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
“…In endothelium, Nrp1 enhances VEGF-mediated phosphorylation and signaling via VEGFR2 (18)(19)(20) and enhances VEGF-induced endothelial permeability (18), chemotaxis (18,19), proliferation, and cell survival (19). Emerging data suggests that although semaphorins can modulate endothelial signaling by competitively inhibiting VEGF signaling (21), they may have independent effects on endothelial function (22,23).…”
mentioning
confidence: 99%
“…77,78 Similarly, Sema3F inhibits cell spreading and migration in breast carcinoma, melanoma and ECs, resulting in reduced metastatic dissemination. [78][79][80] Furthermore, since NP-1 is a receptor for both class III semaphorins and VEGF, class III semaphorins may function as antiangiogenic factors by competitively interfering with VEGF receptors. 68 …”
Section: Sema7a: a Semaphorin Involved In Inflammatory Responses Via mentioning
confidence: 99%